Snake venom proteins and coagulopathy caused by snakebite - Mahdi Babaie (Journal of Birjand University of Medical Sciences, 2021)
Snakebite affects around 3 or 4 million humans annually leading to more than 100,000 deaths. Coagulopathy is one of the significant causes of both morbidity and mortality in these patients. Accordingly, it is of utmost importance to diagnose and treat coagulation disorder due to bites; in addition, it is accompanied by various clinical aspects, such as pre-coagulation, fibrinogen coagulation time, fibrinolytic, platelet activation, anticoagulant, thrombotic, and bleeding. The main cause of coagulopathy caused by snakebite is the presence of compounds found in snake venom. These compounds are mostly proteins with enzymatic activity and high stability; moreover, they rapidly react with factors in the blood circulatory system and disrupt their correct functioning. Regarding the snake venom compounds, especially their proteins, it should be mentioned that different snakeschr('39') venoms have different proteins, which can have a role in coagulation or anticoagulation depending on its amount. The coagulant proteins are subclassified as clotting factor activators and thrombin-like enzymes. The anticoagulant proteins can prevent blood clotting leading to coagulopathy and include phospholipases A2, fibrinolytic, protein C activator, and L-amino acid oxidase (enzymatic anticoagulants) or C-type lectin-like proteins, three-finger toxins (TFTs), and proteinase inhibitors (nonenzymatic anticoagulants). All of these factors cause coagulopathy due to snake bites, which is a clinically important phenomenon and should be carefully examined; otherwise, it would be difficult to make the diagnosis and treatment process. If untreated, coagulopathy can develop quickly and lead to the patientchr('39')s death.